The expression can be simplified to: 7x+4y
the simplest form of 5x + 3y +2x - 6y is 7x-3y
It's just a mathematical polynomial: 7x + 3y.
7x = -3y + 12
7x + 3y = 42 can be converted to slope intercept form using the formula y = mx + b. First, get 3y on to the outside. -3y = 7x - 42 Divide everything by -3. You are left with y = 7/3x + 14
The standard form is 7x + 2y - 3 = 0
The given expression can be simplified to: 7x+4y
x+7x+3y-y =8x+2y =2(4x+y)
What is the slope-intercept form of 7x-3y equals 4
There are 3 terms in the algebraic expression of: 3y+9+7x
(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y
7x+y=6